On the endomorphisms of translation modules of polynomials - Bodnarchuk, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 2000)
We determine the structure of a ring of endomorphisms of a translation module whose structure is determined by a group of translations of an affine space that acts by means of displacement on a polynomial algebra.